ANALISIS PERHITUNGAN PAJAK PERTAMBAHAN NILAI SEBELUM DAN SESUDAH UNDANG-UNDANG HARMONISASI PERPAJAKAN NOMOR 7 TAHUN 2021 GUNA MENENTUKAN PAJAK PERTAMBAHAN NILAI TERUTANG - Wati, Erika Kusuma; Sahara, Khasanah; Suaidah, Imarotus (Jurnal Ilmiah Cendekia Akuntansi; Vol 8 No 2 (2023): April, 2023)
The government carry out economic recovery in various sectors during Coronavirus Disease of 2019 (Covid-19) pandemic, which one is tax sector. Tax as a crucial role holder in state revenue requires the government to increase state revenue targets and make taxpayers feel fair with the stipulation of HPP Law No. 7 of 2021 dated 29 October 2021. The update that has occurred is the change in the rate of imposition of Value Added Tax (VAT) from 10 % to 11% as of April 2022 which will affect the Value Added Tax Payable.The purpose of this research to find out the calculation of VAT before and after the HPP Law No. 7 of 2021 to determine the VAT payable. Comparing VAT rates based on Law No. 42 of 2009 with HPP Law No. 7 of 2021 using quantitative descriptive method by processing sales and purchase data records of CV ELRAYA for January-July 2022 into tariff formula VAT before and after the HPP Law No 7 of 2021 and the formula for VAT payable. The conclusion is the VAT payable that must be borne by CV ELRAYA is Rp. 49,682,036, reported on the correction SPT and deposited at the Pratama Kediri Tax Service Office, with this conclusion advice can be given for tax planning in order to save and minimize the tax expense in the next period.